Evaluation of relationship between bone mineral density and fragility fracture in perimenopausal women between 40-58 years of age: a hospital based prospective observational study - Kumar, Arvind; Pheroz, Mozammil; Chopra, Rajesh K.; Tungoe, Benthungo; Kumar, Narendra; Aggarwal, Yatish; Sarwar, Samrin; Soni, Manoj (International Journal of Research in Orthopaedics, 2019)
Background: At present the risk assessment for osteoporosis using low bone mineral density (BMD) is based on data obtained from elderly females, largely ≥ 65 years of age. The risk factors for low peak bone mass or accelerated bone loss that occurs during perimenopausal phase is ignored in this risk assessment. Osteoporosis is found to occur at a relatively younger age in the Indian population. Although lower BMD values have an established identity as a major risk factor for fractures in postmenopausal women, we endeavour to evaluate relationship between bone mineral density and fragility fracture in perimenopausal women. Methods: 65 Patients were recruited for the study. After X-ray of involved part, patients were divided into cases (with fracture, n=33) and control (no bony injury, n=32). All patients underwent dual energy X-ray absorptiometry (DEXA) scan. Results of DEXA scans were evaluated in both the groups. BMD was expressed in g/cm2. Results: 33 patients (50.77%) were diagnosed as fracture, 32(49.23%) had no bony injury. Threshold bone mineral density (BMD) for fragility fracture found out asfor L1, cut off ≤0.767. For L2, cut off ≤0.829. For L3, cut off ≤0.811. L4, cut off ≤0.798. For L1-L4, cut off ≤0.845. For left femur total hip, cut off ≤0.918. For left forearm-total, cut off ≤0.411. For right femur total hip-cut off ≤0.795. For right forearm-total, cut-off≤0.382. Conclusions: Perimenopausal women having BMD below threshold for involved site are at risk of fragility fracture and should be given prophylactic treatment to improve bone mineral density.